Building a static farm level spatial microsimulation model for rural development and agricultural policy analysis in Ireland. (2nd June 2009) - Hynes, Stephen; Morrissey, Karyn; O'Donoghue, Cathal; Clarke, Graham
Using statistical matching techniques, economists can now create attribute rich datasets by matching across the common variables in two or more datasets. The farm level spatial microsimulation model developed in this paper uses one of many combinational optimisation techniques – simulated annealing – to match the Irish Census of Agriculture to the 2005 Irish National Farm Survey (NFS). Using the new spatially disaggregated farm population microdata this paper then briefly analyses the impact of future Common Agricultural Policy (CAP) reform on the distribution of family farm income in rural Ireland.